Effectiveness of Online Population Administration Services at the Department of Population and Civil Registration of Garut Regency - Ikeu Hikmawati; Fingki Fitriani; Imron Rosadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Since 2020, the Department of Population and Civil Registration of Garut Regency has implemented online population administration services. However, in its implementation, several problems have still been identified. Therefore, this study aims to determine the effectiveness of these online population administration services. This research employs a qualitative (naturalistic) method with a descriptive approach, in which the researcher acts as the research instrument and collects data through observation, interviews, and documentation. The results show that in the productivity dimension, the number of online service applications is lower than manual service applications, and similarly, the number of documents issued through online services is lower than those issued manually. In the quality dimension, the quality of online population administration products is fairly good; however, the quality of online services is not yet satisfactory, as it is often constrained by facilities and infrastructure. In the efficiency dimension, online population administration services shorten service time and simplify procedures. In the capability dimension, online services require the public to possess adequate information technology skills and require officers to be responsive. In the benefit dimension, the community perceives the benefits of online population administration services and responds positively to them. The study also identifies inhibiting factors related to inadequate facilities and infrastructure, limited public understanding, and the lack of technological resources among community members.